Patient involvement in pressure ulcer prevention and adherence to prevention strategies: An integrative review. (January 2020) - Ledger, Lisa; Worsley, Peter; Hope, Jo; Schoonhoven, Lisette
Abstract: Background: Chronic wounds including pressure ulcers represent a significant burden to patients and healthcare providers. Increasingly patients are required to self-manage their care but patient adherence to prevention strategies is a significant clinical challenge. It is important to increase understanding of the factors affecting patients' ability and willingness to follow pressure ulcer prevention interventions. Objectives: To investigate from a patient perspective the factors affecting adherence to pressure ulcer prevention strategies. Design: Integrative literature review. Data sources: A systematic search of electronic databases (Athens, Pub Med, Web of Science, Science Direct, AMED, CINAHL, Cochrane Library, PsychInfo, Google Scholar, Delphis) was initially conducted in May 2017 (repeated August 2018). Review methods: The methodological quality was assessed using the Critical Appraisal Skills Programme (CASP) principles. The Noticing, Collecting, Thinking (NCT) model of qualitative data analysis was used to identify key themes. Results: A total of twelve studies met the inclusion criteria and were included in the review. The majority of studies were qualitative and three key themes were identified: (i) individual/daily lifestyle considerations, (ii) patient involvement in the decision-making process, and (iii) pain and/or discomfort. Conclusion: There is limited research that focuses on the patient view of factors affecting adherence to prevention measures, particularly in community settings. Individual and daily lifestyle considerations and involvement in decision-making around pressure ulcer care are important aspects from the patient perspective. Further research is necessary to explore which factors affect patient adherence in order to improve clinical practice and support patient involvement in preventative strategies.